Acute Abdomen in a Patient with Cancer Pain on Oxycodone - Naomi Kishine; Atsunobu Tsunoda; Seiji Kishimoto; Tomohisa Shoko (Case Reports in Medicine)
Opioids are a mainstay of treatment for moderate to severe cancer pain. At present, oxycodone has fewer adverse effects compared to morphine and is widely used for cancer pain therapy. The adverse effects of oxycodone are similar to morphine and include constipation, nausea, and sedation. However, acute abdominal pain is rarely seen. Here, we describe a cancer patient presenting with acute abdomen with stercoral diarrhea. A 54-year-old man with squamous cell carcinoma of the external auditory canal had been taking oxycodone for pain relief. The patient had taken oxycodone for several months and had never complained of either diarrhea or constipation. After an increase in the dosage of oxycodone, he complained of abdominal distension and constipation. After being administered a laxative, he complained of diarrhea and severe abdominal pain. He visited the emergency department and was diagnosed with acute colonic obstruction caused by severe constipation. He self-medicated with oxycodone at dosages of up to 180 mg/day, and this abrupt increase of oxycodone caused stercoral diarrhea. Finally, total blockage of stool developed, resulting in acute abdomen.